Assessment of hospitals' websites in Portugal - Sarantis, Demetrios; Soares, Delfina Sa; Carvalho, Joana (Frontiers in Public Health, 2022)
Technological advances have highly facilitated the accession of health-related information. As the public search on hospital websites for information and services is increasing, hospitals need to upgrade their websites to meet the high standards and demands of health-care consumers. Today, many hospital websites use a patient-centric approach to promote engagement and encourage interaction for better health-related decision making. However, little is known about the current state of hospital websites in Portugal. This study aims to assess hospital websites in Portugal and offer improvement insights. In this paper, the websites of 132 selected hospitals were thoroughly examined and assessed according to a predefined list of indicators and sub indicators, based on four criteria: technology, content, services and community interaction, defined in the Health Sector Website Assessment Index (HSWAI) instrument. Most of the websites scored satisfactorily in the technology criterion, performed fairly well in providing fundamental content, but showed shortcomings in quality metrics data and online patient services, and most of them fell short in community interaction elements. Overall, the results show that each hospital website must be improved in specific features in order to become effective and efficient. Several of the identified assessment elements (indicators/sub indicators) fall under Sustainable Development Goal (SDG) 3, United Nations health-focused goal, and could be used by governments to assess their progress toward achieving that specific goal. Therefore, this study not only provides a comprehensive and systematic approach that quantitatively measures hospital websites' overall performance, but also contributes to practical applications in terms of worthwhile recommendations for a website that meets patient's demands and hospital's operational needs.